Struktur Modal dan Kinerja Keuangan Holding MIND ID: Efisiensi Biaya sebagai Variabel Mediasi - Ikhsani, Nadifka; Norisanti, Nor; Nurmala, Resa (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
Financial performance is a crucial indicator reflecting a company’s capability to generate profit and maintain business sustainability. In the mining industry, financing decisions and operational cost management are essential factors influencing financial performance. This study aims to analyze the effect of capital structure on financial performance, examine the effect of capital structure on cost efficiency, determine the effect of cost efficiency on financial performance, and evaluate the mediating role of cost efficiency in the relationship between capital structure and financial performance within the Holding Industri Tambang MIND ID from 2021 to 2025. This quantitative explanatory study analyzed quarterly financial report data from publicly listed holding member companies using Partial Least Squares-Structural Equation Modeling (PLS-SEM) executed through SmartPLS 3. The empirical findings reveal that capital structure has a significant negative effect on financial performance, capital structure has no significant effect on cost efficiency, cost efficiency has a significant negative effect on financial performance, and cost efficiency fails to mediate the relationship between capital structure and financial performance. These findings indicate that operational efficiency has not operated as the mediating bridge connecting financial decisions to overall financial performance in MIND ID holding members. Consequently, holding management must establish adaptive debt threshold policies and digitalized field cost controls to sustain profitability during commodity market downturns.